Modern Diagnostic Methods for Early Ddetection of Cervical Diseases - N.O. Navruzova; Z.Sh. Kurbanova (Genius Journals, 2022)
This article describes the results of simple and extended colposcation, which was held among 131 women in repoductive age who consulted with different gynecological diseases. The result of the studies shows that 67,9% women had a diffirent pathological change cervix of the uterus. Of them 24,4% women had not any complaints and clinical sign.
Keywords: Colposcopy; diseases; women; uterus